1989
DOI: 10.3758/bf03210857
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle perception by ongenitally blind children

Abstract: The ability to perceive objects from a distance and navigate without vision depends principally on auditory information. Two experiments were conducted in order to assess this ability in congenitally blind children aged 4 to 12 years who had negligible amounts of visual experience or formal mobility training. In Experiment 1, children walked along a sidewalk toward a target location to get some candy. A box was placed along the path on some trials, and the children were instructed to avoid the box if it was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
1
37
0
1
Order By: Relevance
“…Given that visual cues play a crucial role in capturing and organizing spatial formation, it has been assumed that blind individuals (and in particular, those who are born with profound blindness) would be impaired in creating an accurate mental spatial representation of their surroundings (von Senden, 1960; Ashmead et al, 1989; Thinus-Blanc and Gaunet, 1997; see also Blasch et al, 1997 for further discussion). It is thus of interest that both early and late blind participants showed similar levels of performance in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that visual cues play a crucial role in capturing and organizing spatial formation, it has been assumed that blind individuals (and in particular, those who are born with profound blindness) would be impaired in creating an accurate mental spatial representation of their surroundings (von Senden, 1960; Ashmead et al, 1989; Thinus-Blanc and Gaunet, 1997; see also Blasch et al, 1997 for further discussion). It is thus of interest that both early and late blind participants showed similar levels of performance in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Blind individuals typically undergo formal instruction referred to as orientation and mobility (O&M) training as a means of learning how to navigate independently through the environment. Unlike the sighted, blind individuals must rely on other sensory channels (such as hearing, touch, and proprioception Thinus-Blanc and Gaunet, 1997) to gather relevant spatial information for orientating, route planning, and path execution (Strelow, 1985; Ashmead et al, 1989; Loomis et al, 1993; Long and Giudice, 2010). The resultant mental representation of the surrounding space is referred to as a spatial cognitive map (Strelow, 1985), and generating an accurate and robust mental map is considered essential for efficient travel (Siegel and White, 1975; Blasch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that blind people are better at echolocation than those who are sighted (see Teng and Whitney 2011, for a summary) and one possible reason for this might be that blind people are generally more sensitive to acoustic reverberations (Dufour et al 2005;Kolarik et al 2013). There are also substantial differences in echolocation capacities between blind people, with congenital blind children often needing no training (Ashmead et al 1989), and people who lose vision earlier in life showing better performance (Teng et al 2012). In sighted people Teng and Whitney (2011) found that all of their sighted novices improved their echolocation ability with regard to size discrimination across multiple sessions, but also that there was variability across participants.…”
mentioning
confidence: 99%
“…Such findings are usually associated with the precedence effect in sound localization (Wallach, Newman, & Rosenzweig, 1949;see Zurek, 1987, for a review). The precedence effect has been the topic of extensive physiological (Cranford & Oberholtzer, 1976;Yin & Litovsky, 1995), developmental (Clifton, Morrongiello, & Dowd, 1984;Morrongiello, Clifton, & Kulig, 1982), applied (Blauert, 1989;Muncey, Nickson, & Dubout, 1953;Snow, 1954), and clinical (Ashmead, Hill, & Taylor, 1989;Ashmead et al, 1998;Hochster & Kelly, 1981) study within the hearing sciences.…”
mentioning
confidence: 99%